Pillar-supported vacuum insulation panel with multi-layered filler material. (November 2016) - Choi, Bongsu; Yeo, Inseok; Lee, Jaehyug; Kang, Won Kyeong; Song, Tae-Ho
Highlights: Pillar-supported vacuum insulation panel is proposed. Heat transfer and mechanical stability are investigated for pillar-supported VIP. MPS-supported VIP has twice better insulation performance than existing VIPs. Abstract: Vacuum insulation panels (VIPs) have about ten times greater insulation performance compared with conventional insulators, and it is highly affected by the filler material. In this paper, pillar-supported vacuum insulation panel is proposed to release the filler material from the pressing load, thereby significantly decreasing the effective thermal conductivity. It is composed of the support structure and the multi-layered filler material. The support structure consists of the cover plates and pillars, as they sustain the atmospheric pressure. Thus, mechanical stability and heat transfer are considered together in the design stage. Multi-pass support (MPS) is introduced to further decrease the conduction through the pillar effectively. Also, the multi-layered filler material is composed of the glass wool sheets and radiation shields of low emissivity. The effective thermal conductivity of the tested specimen measures 1.18 mW/m K with vacuum guarded hot plate (VGHP), which shows twice better insulation performance than existing VIPs.